4CPS-375 Excessive polypharmacy and other determinants for unplanned hospital admissions. (14th March 2021) - Hias, J; Hellemans, L; Xu, D; Nuyts, S; Vaes, B; Spriet, I; Tournoy, J; Van Der Linden, L
Abstract : Background and importance: Unwanted polypharmacy has been associated with avoidable harm (eg, unplanned hospital admissions (UHAs)), especially in older adults. Clinical pharmacy interventions have been developed to reduce UHAs. Yet it remains unclear which population derives the largest benefit of such interventions. Aim and objectives: The aim of this study was to identify determinants for UHAs in community dwelling adults. Material and methods: A retrospective study was performed, using data from a linked database consisting of the Integrated Computerised Network and the InterMutualistic Agency database. Patients aged 40 years or older with data available for the years 2013–2015 were included. Patients who died or were admitted to a nursing home were excluded. An index date was defined as the last general practitioner (GP) contact in 2014. The preceding 12 months were used to collect the determinants. For the occurrence of a UHA, a period of 12 months after the index date was used. To select determinants for inclusion in the multivariable model ( table 1 ), a univariate logistic regression model was fitted on each predictor with the outcome UHA as the response. Systolic blood pressure, alanine aminotransferase and potassium were non-significant at the level of 0.2 and hence were excluded from the multivariable model. Results: 40 411 patients were included in the project and 2126 (5.26%) patients had at least one UHA. Mean age was 58.3 (±12.3) years. Results of the multivariable logistic regression model are summarised in table 1 . Conclusion and relevance: The model identified seven determinants as associated with UHA: excessive polypharmacy, male gender, number of comorbidities, older age, low haemoglobin level and prior hospital and GP visits. References and/or acknowledgements: Conflict of interest: No conflict of interest